Recorded Scan Times Can Limit the Accuracy of Sedimentation Coefficients in Analytical Ultracentrifugation - Zhao, Huaying (2013)
We report systematic and large inaccuracies in the recorded elapsed time in data files from the analytical ultracentrifuge, leading to overestimates of the sedimentation coefficients of up to 10%. This far exceeds previously considered factors contributing to the uncertainty in this parameter, and has significant ramifications for derived parameters, such as hydrodynamic shape and molar mass estimates. The source of this error is at present unknown, but we found it to be quantitatively consistent across different instruments, increasing with rotor speed. Furthermore, its occurrence appears to correlate with the use of the latest data acquisition software from the manufacturer, in use in some of our laboratories for nearly two years. Many of the recently published sedimentation coefficients may need to be re-examined. The problem can be easily recognized by comparing the file time-stamps provided by the operating system with the elapsed scan times recorded within the data files. We therefore implemented a routine in SEDFIT that can automatically examine the data files, alert the user to significant discrepancies, and correct the scan times accordingly. This eliminates errors in the recorded scan times.